PELATIHAN PENGGUNAAN ALAT UKUR DAN ALAT PEMERIKSAAN SEBAGAI UPAYA PENINGKATAN KAPASITAS GURU SMK BULUKUMBA - Nurlaela; Aminuddin; Fiskia Rera; Rusli Ismail; Asmah Adam (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Training for teachers aims to ensure that educators have professional skills and can maximize the learning process in the classroom. Mechanical measuring instruments are tools used to measure various parameters in mechanics, such as length, angle, mass, speed, pressure and force, the measurement results determine the quality of a product. One measuring instrument that has a high level of accuracy is a micrometer. Training on the use and reading of measuring instruments is an effort to improve and refresh teachers' abilities in using micrometer measuring instruments. The micrometer that will be displayed is a measuring instrument that is more widely used in industry. This activity begins with: (1) Observation (2) Concept (3) Implementation (4) Evaluation (5) Further training. The result of this training was an increase in teachers' ability to use measuring instruments, as well as efforts by the school to equip facilities, especially measuring instruments, at the school. Keywords: Training, Varnier Caliper, Micrometer, Inspection Tool, Teacher